A Green Route to a Na2FePO4F-Based Cathode for Sodium Ion Batteries of High Rate and Long Cycling Life - Deng, X.; Shi, W.; Sunarso, J.; Liu, M.; Shao, Zongping (American Chemical Society, 2017)
© 2017 American Chemical Society. Sodium ion batteries (SIBs) are considered one of the most promising alternatives for large-scale energy storage due largely to the abundance and low cost of sodium. However, the lack of high-performance cathode materials at low cost represents a major obstacle toward broad commercialization of SIB technology. In this work, we report a green route strategy that allows cost-effective fabrication of carbon-coated Na 2 FePO 4 F cathode for SIBs. By using vitamin C as a green organic carbon source and environmentally friendly water-based polyacrylic latex as the binder, we have demonstrated that the Na 2 FePO 4 F phase in the as-derived Na 2 FePO 4 F/C electrode shows a high reversible capacity of 117 mAh g -1 at a cycling rate of 0.1 C. More attractively, excellent rate capability is achieved while retaining outstanding cycling stability (~85% capacity retention after 1000 charge-discharge cycles at a rate of 4 C). Further, in operando X-ray diffraction has been used to probe the evolution of phase structures during the charge-discharge process, confirming the structural robustness of the Na 2 FePO 4 F/C cathode (even when charged to 4.5 V). Accordingly, the poor initial Coulombic efficiency of some anode materials may be compensated by extracting more sodium ions from Na 2 FePO 4 F/C cathode at higher potentials (up to 4.5 V).